Insights from blended mobility: Combining COIL & short-term study abroad to enhance international business communication learning - Michael Meredith (EuroAmerican Journal of Applied Linguistics and Languages)
Rapid cultural and digital transformations are disrupting higher education. Focusing on unique areas referred to as “human intelligence” (HI) is critical to meet students’ changing needs. This paper explores the design, pedagogy, and outcomes of an international business communication course integrating a blended mobility model. This study investigates student outcomes in a blended mobility format combining a COIL course with a brief study abroad experience, culminating in a cross-cultural team presentation to a real business client. Content analysis of student reflections identifies core learning outcomes, comparing and expanding upon blended mobility “employability skills”. Five additional skills emerged, consistent with intercultural competency communication research as well as ten sub-themes related to belonging. Findings highlight the potential of blended mobility to foster “HI” professional skills as well as a sense of belonging among student participants.